The Right to the City: The Housing Rights Movement of Bangbua Community - Sang-arun, Nattapon (Journal of Architectural/Planning Research and Studies (JARS), 2019)
This study aims to answer the question ‘‘What are the Bangbua community’s bargaining processes to reach solutions to housing insecurity? And how do such processes bring solidarity to the community?’’ The research design is to survey and collect data from the community and also to analyze it, using the concepts of the Right to the City and social movement. It finds that Bangbua community’s processes are a kind of social movement and informed in part by the Right to the City. Moreover, it could serve as a model solution for housing insecurity in other poor urban communities.